Postpartum Exudation of Idiopathic Quiescent Macular Neovascularization: A Narrative Review with a Related Case Report - Livio Vitiello; Maddalena De Bernardo; Ilaria De Pascale; Giulio Salerno; Alfonso Pellegrino; Nicola Rosa (Life)
The abnormal growth of irregular new blood vessels into the subretinal or intraretinal space is known as macular neovascularization (MNV). People over 50 are often affected by this disorder, which is typically brought on by age-related macular degeneration. In addition, MNV can be found in people under 50 years of age, who may present primary ophthalmic diseases such as pathological myopia, angioid streaks, traumatic choroidal rupture, or suspected ocular histoplasmosis syndrome. However, it is important to consider a specific set of young individuals who may develop MNV even in the absence of pathological myopia or other identifiable inflammatory, peripapillary, post-traumatic, or degenerative fundus abnormalities. This latter condition is classified as idiopathic MNV. After a literature review focused on young patients affected by one of these two clinical entities, we report the case of a Caucasian young woman suffering for four years from an idiopathic and quiescent MNV that started exuding after childbirth, probably due to the induction with oxytocin, and was treated with intravitreal Aflibercept 2 mg injections.